A New Hasidism: Roots - Mayse, Ariel Evan; Green, Arthur, 1941- (Book collections on Project MUSE., 2019)
"In this ground-breaking presentation of Neo-Hasidic philosophy, Green and Mayse draw together the writings of five great twentieth-century European and American Jewish thinkers--Hillel Zeitlin, Martin Buber, Abraham Joshu Heschel, Shlomo Carlebach, Zalman Schachter-Shalomi, plus some of Green's own youthful writings -- sharing each of their reflections on the inner life of the individual and their dreams of creating Neo-Hasidic spiritual communities"--